Islamism, Crisis and Democratization Implications of the World Values Survey for the Muslim World - Solomon, Hussein; Tausch, Arno (Perspectives on Development in the Middle East and North Africa (MENA) Region, 2020)
XV, 247 p. 21 illus., 13 illus. in color.